Keragaan Kapas Bronesia 1 dan Seleksi Beberapa Jenis Pupuk Berdasarkan Karakter Agronomi - Yamin, Mayasari; Nur Qadri, Sri; Desiah Pradilia, Andi; Hama, Sartia (Jurnal Galung Tropika, 2024)
Indonesia is the sixth largest cotton importer and the ninth largest cotton user in the world. Therefore, efforts are needed to form new superior varieties, starting with determining the performance of cotton as a candidate for the formation of new superior varieties.This research aims to obtain cotton seeds for seed multiplication the following year, producing good brown cotton performance based on agronomic characteristics and the best type of organic fertilizer in increasing the growth of cotton plants. This study was conducted at the KP. Faculty of Agriculture, Animal Husbandry, and Fisheries, Muhammadiyah University of Parepare from June to October 2023. This study used a randomized block design with five repetitions. The treatments used were 4 types of fertilizers, namely chemical fertilizers, cocoa shell waste compost, goat manure compost, and Eco Glasum organic fertilizer. Thus, there were 20 experimental units. The observation parameters observed and measured were plant height (cm), number of leaves (strands), number of generative branches, pollen phenotype and cotton stomata, and age of flower blooming (DAP). Observation data were processed using the SAS 9.0 and Minitab 14 applications. The results showed that agronomic characters were not significantly different except for the number of leaves. The type of eco glasum fertilizer showed the best performance for the characters of plant height, leaf greenness, number of flowers, number of flowers blooming. Direct selection using scatterplot shows the best eco glasum fertilizer on the character relationship between the number of flowers vs. leaf greenness (R = 0.049 + 2.305X) and the number of flowers vs. plant height (R = 1.427 + 36.57X). Eco Glasum is a modification of solid fertilizer consisting of three types of seaweed, namelyEucheuma cottoni, Glacilaria sp., Sargasum sp. and modified by the addition of natural ZPT (Plant Growth Regulators) which are then fermented.